Response of short-term heat shock on photosynthetic activity of soil crust cyanobacteria - Kvíderová, Jana; Kumar, Dhanesh (Protoplasma, 2020)
Short-term heat exposure in tropical regions can generate severe stress in the photosynthetic activity of soil crust cyanobacteria. We investigated the responses of two filamentous cyanobacteria, Scytonema tolypothrichoides and Tolypothrix bouteillei, to 1hr exposure at 35, 45, and 55 °C using variable chlorophyll fluorescence. Protocols for maximum quantum yield (FV/FM) and dark recovery of chlorophyll a fluorescence (OJIP) transient were applied. Heat exposure caused damage to the donor side of PSII, indicated by a decrease in FV/FM and a rapid increase in F0. After heat stress, photochemical energy utilization (φPo, φETo, and φRE1o) declined and energy dissipation (φDIo) increased. At 45 °C, the photosynthetic apparatus was reversibly damaged, since full recovery was observed after 7 days of relaxation. S. tolypothrichoides was more resistant to heat stress than T. bouteillei, confirming better adaptation to higher temperatures as observed in growth experiments.
Keywords: Photosynthesis; Heat stress; pravděpodobnost; reakce na tepelný šok; bakteriální proteiny; Photosynthetic Reaction Center Complex Proteins; Fluorescence; OJIP transient; časové faktory; sinice; Heat-Shock Response; Quantum Theory; fotosyntetická reakční centra (proteinové komplexy); chlorofyl a; kvantová teorie; půdní mikrobiologie; transport elektronů; Bacterial Proteins; Chlorophyll A; fluorescence; Cyanobacteria; fotosyntéza; Electron Transport; Time Factors; Probability; Soil Microbiology